Question Number 115072 by A8;15: last updated on 23/Sep/20

Commented byA8;15: last updated on 23/Sep/20

please help with the solution

Answered by 1549442205PVT last updated on 23/Sep/20

Opening brackets we get  S=2020−(2019−(2018−(2017−  (2016−(....(2−1)...)  =2020−2019+2018−2017+...  +2−1=(2020−2019)+(2018−2017)+  +...+(2−1)=1+1+...+1=1010  (Since all 2020 terms⇒1010 sums)

Commented byA8;15: last updated on 23/Sep/20

thank you sir

Answered by JDamian last updated on 23/Sep/20

d) 1010

Commented byA8;15: last updated on 23/Sep/20

how ? I need a solution